Single-cell RNA sequencing reveals the heterogeneity and interactions of immune cells and Müller glia during zebrafish retina regeneration - Hui Xu; Lining Cao; Yuxi Chen; Cuiping Zhou; Jie Xu; Zhuolin Zhang; Xiangyu Li; Lihua Liu; Jianfeng Lu (Neural Regeneration Research)
Inflammation plays a crucial role in the regeneration of fish and avian retinas. However, how inflammation regulates Müller glia (MG) reprogramming remains unclear. Here, we used single-cell RNA sequencing to investigate the cell heterogeneity and interactions of MG and immune cells in the regenerating zebrafish retina. We first showed that two types of quiescent MG (resting MG1 and MG2) reside in the uninjured retina. Following retinal injury, resting MG1 transitioned into an activated state expressing known reprogramming genes, while resting MG2 gave rise to rod progenitors. We further showed that retinal microglia can be categorized into three subtypes (microglia-1, microglia-2, and proliferative) and pseudotime analysis demonstrated dynamic changes in microglial status following retinal injury. Analysis of cell–cell interactions indicated extensive crosstalk between immune cells and MG, with many interactions shared among different immune cell types. Finally, we showed that inflammation activated Jak1–Stat3 signaling in MG, promoting their transition from a resting to an activated state. Our study reveals the cell heterogeneity and crosstalk of immune cells and MG in zebrafish retinal repair, and may provide valuable insights into future mammalian retina regeneration.